The impact of portfolio on EFL learners’ metacognition and writing performance - Majid Farahian; Farnaz Avarzamani (Cogent Education, 2018)
The present study seeks to investigate the role of portfolios in EFL (English as a Foreign Language) writers’ metacognition as well as their writing skill. Therefore, the participants were assigned to two groups (experimental and control). The students in both groups received a writing test, a researcher-made Metacognitive Writing Questionnaire (MWQ), and a students’ attitude questionnaire for pre- and post-test. The experiment group was provided with specific guidelines and reflection sheets. The results indicated that portfolios significantly contribute to empowering both the metacognition and writing proficiency of EFL learners. As to the learners’ attitudes toward EFL writing assessment, it was generally revealed that portfolio students have a positive view of formative assessment, and teacher/peer feedback. The study suggests that not only can portfolios be used as assessing tools, but also they are indirect means of introducing self-reflection into writing courses.